Model to predict dimethyl carbonate synthesis through transesterification of ethylene carbonate with methanol in fixed-bed reactor - Abimanyu, H; Yoo, KS; Moon, DJ; Ahn, BS; Song, J (ELSEVIER SCIENCE INC, 2005)
Dimethyl carbonate synthesis through the transesterification reaction of ethylene carbonate (EC) with methanol was studied over a heterogeneous K/MgO catalyst. The experiments were conducted in a fixed-bed reactor at temperatures from 100 to 140 degrees C and feed molar ratios (methanol to ethylene carbonate) from 4 to 8 with various feed flow rates from 2.5 to 25 mL/h, i.e., equal to LHSV from 0.1 to 10 h(-1). The EC conversion increased upon increasing the reaction temperature and the feed molar ratios, but it decreased upon increasing the feed flow rate. A model to predict the process was developed and correlated with the experimental data. This formulated model was in good agreement with the experimental values.
Keywords: CATALYSTS; DIMETHYLCARBONATE; DIOXIDE; GLYCOL